Educational Content Aimed at the Formation of Lexical Competence of Future Specialists in the Field of Technology - Sabitova Iroda Srajiddinovna (Web of Journals Publishing, 2023)
The article is devoted to the problems of teaching professionally directed vocabulary in an economic university. It is noted that the difficulties in mastering vocabulary, especially professionally oriented ones, are associated with the insufficient development of modern technologies for teaching vocabulary. In this regard, the author made an attempt to create his own technology for teaching professionally oriented vocabulary in an economic university. The learning algorithm is described, which consists of three main stages (introductory, forming, improving); examples of tasks for exercises to consolidate the studied vocabulary are given; the system of work on the introduction and consolidation of economic vocabulary is shown. The technology developed by the author contains a system of exercises differentiated by difficulty levels, which can be used by students of economic universities.
Keywords: professional vocabulary, economic university, learning technology, learning algorithm, exercise system.